2016
DOI: 10.1016/j.jor.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive photo acoustic approach for human bone diagnosis

Abstract: The existing modalities of bone diagnosis including X-ray and ultrasound may cite drawback in some cases related to health issues and penetration depth, while the ultrasound modality may lack image quality. Photo acoustic approach however, provides light energy to the acoustic wave, enabling it to activate and respond according to the propagating media (which is type of bones in this case). At the same time, a differential temperature change may result in the bio heat response, resulting from the heat absorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the more specific context of bone imaging, photoacoustic imaging has demonstrated potential to non-invasively diagnose different types of bones, including cancerous bones (Thella et al 2016). In addition, photoacoustic technology previously proved to be sensitive to minor variations of the cortical bone density (Lashkari & Mandelis 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the more specific context of bone imaging, photoacoustic imaging has demonstrated potential to non-invasively diagnose different types of bones, including cancerous bones (Thella et al 2016). In addition, photoacoustic technology previously proved to be sensitive to minor variations of the cortical bone density (Lashkari & Mandelis 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The control parameters in these modalities are important in the non-invasive approaches. 10,11 This may include the frequency, penetration depth, the incident power the output temperatures, etc. The penetration depth should be long enough to enable the power transmission via the human materials such as bones, skin, blood, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thella et al [46] demonstrated that photoacoustic imaging shows potential for the noninvasive diagnosis of various bone types, including bones containing cancer. In addition, photoacoustic technology has been found to be sensitive to minor variations in cortical bone density [47].…”
Section: Applications Of Photoacoustic Imaging For Spinal Surgerymentioning
confidence: 99%